2019 Annual review and planning meeting of BASICS project - CGIAR Research Program on Roots, Tubers and Bananas (2019)
The BASICS Annual Review and Planning Meeting (ARPM) 2019 was held in IITA Headquarters in Ibadan, Nigeria from 11-13 March 2019. The Meeting was attended by around 70 participants from Nigeria and several other countries. The participants included breeders, food and crop scientists, project managers, national policy experts, R&D managers, donor, social scientists and company representatives. Proceedings of the Annual Meeting will be published on the BASICS website (http://www.rtb.cgiar.org/basics/) The purpose of the current summary is to synthesize some of the discussions, conclusions and points for future action. There are links within this document to access the actual presentations made during the ARPM. The main aim of the ARPM was to reiterate the project vision, share what has been done, what is to be done in 2019 and brainstorm on what needs to be done over a possible next phase of activities to achieve the goal of developing an economically sustainable seed system for cassava in Nigeria. Towards this, the ARPM over the three days was planned with the following objectives listed below.